Effect of polymer type on the dynamics of phase inversion and drug release in injectable in situ gelling systems - Liu, Hui (2013)
The objective of this study was to evaluate the effect of the nature of the polymer on the dynamics of phase inversion and drug release in an in situ forming gel drug-delivery system composed of a biodegradable polymer and the solvent N-methyl-2-pyrrolidone (NMP), with metoclopramide monohydrochloride (metosalt) used as a low-molecular-weight model drug. Injection of this solution into an aqueous medium leads to the formation of a solid gel due to the rapid solvent/water exchange, followed by sustained release of the incorporated drug. The release of solvent from the injectable gel into phosphate buffer, which influences the polymer precipitation rate, was investigated as a function of the type of polymer using UV-Vis spectrophotometry. The cross-sectional gel morphology and its water uptake were characterized to relate the initial burst release (and thus the dynamics of phase inversion) to the polymer lactide/glycolide ratio and to the end-group characteristics. The results show that the phase inversion of hydrophobic polymers (e.g., PdlLA) occurs faster than the phase inversion of relatively more hydrophilic polymers (e.g., PLGA75/25, RG502 and RG502H). Three of the four polymers exhibit a four-phase profile, with the characteristics of each phase dependent on the hydrophobicity and degradation kinetics of the individual polymer.